Cannae 216 BC : Hannibal smashes Rome's army - Healy, Mark, 1953-; McBride, Angus; Hook, Richard, 1938-2010 (London : Osprey Military, 1994)
"Cannae is rightly regarded as one of history's greatest battles. Hannibal's stratagem has become a model of the perfectly fought battle and is studied in detail at military academies around the world. At Cannae, the Romans confronted Hannibal with an army of 80,000 infantry and 6,000 cavalry. Hannibal faced them with 40,000 foot soldiers and 10,000 horses. The engagement that followed was a masterpiece of battlefield control. By the end of the conflict the Romans had lost 47,500 infantry and 2,700 cavalry, with a further 19,300 captured.--Page 4 of cover.
The opposing leaders -- The opposing armies -- 218 : Ticinus and Trebbia -- 217 : Lake Trasimene -- 217-216 : The Fabian strategy -- The approach to Cannae -- The Battle of Cannae -- Aftermath -- Chronology -- A guide to further reading -- The battlefield today -- Wargaming Cannae.
Cover title.
Includes bibliographical references (page 90).
Keywords: Hannibal, -- 247 B.C.-182 B.C.; 216-216 B.C; Cannae, Battle of, Italy, 216 B.C.; Italy; Rome -- History, Military -- Republic, 265-30 B.C.; Military operations; Italy; Roman Empire